2021
DOI: 10.3354/ame01963
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community dynamics during a harmful algal bloom of Heterosigma akashiwo

Abstract: Phytoplankton bloom events result in distinct changes in the composition and availability of nutrients as well as physical conditions within aquatic ecosystems, resulting in significant effects on bacterial communities. Using a metabarcoding approach, this study investigated the effect of a harmful algal bloom (HAB) of Heterosigma akashiwo in the Sundays Estuary, South Africa, on bacterial community structures in this estuarine ecosystem over an entire bloom event. The occurrence of bacterial lineages occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Previous work has identified consistent taxonomic shifts in portions of the heterotrophic community in response to 'typical' sized blooms (Teeling et al, 2016;Wilson et al, 2021) and succession in the bacterial community has been observed following a HAB of Heterosigma akashiwo (Matcher et al, 2021). In particular, members of Flavobacteriales (Kirchman, 2002;Avci et al, 2020;Ferrer-Gonzalez et al, 2020;Matcher et al, 2021;Wilson et al, 2021) and Rhodobacterales Buchan et al, 2014) have both been shown to increase in response to phytoplankton-derived polysaccharides from variously sized blooms. A majority of work analyzing microbial responses to phytoplankton blooms, however, are either based on time series with 'typical' seasonal and small non-seasonal blooms (Wear et al, 2015;Teeling et al, 2016;Wilson et al, 2021) or based on opportunistic encounters with large-scale harmful blooms (Matcher et al, 2021), which makes comparing the magnitude of change in microbial taxonomy and function to HABs difficult.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous work has identified consistent taxonomic shifts in portions of the heterotrophic community in response to 'typical' sized blooms (Teeling et al, 2016;Wilson et al, 2021) and succession in the bacterial community has been observed following a HAB of Heterosigma akashiwo (Matcher et al, 2021). In particular, members of Flavobacteriales (Kirchman, 2002;Avci et al, 2020;Ferrer-Gonzalez et al, 2020;Matcher et al, 2021;Wilson et al, 2021) and Rhodobacterales Buchan et al, 2014) have both been shown to increase in response to phytoplankton-derived polysaccharides from variously sized blooms. A majority of work analyzing microbial responses to phytoplankton blooms, however, are either based on time series with 'typical' seasonal and small non-seasonal blooms (Wear et al, 2015;Teeling et al, 2016;Wilson et al, 2021) or based on opportunistic encounters with large-scale harmful blooms (Matcher et al, 2021), which makes comparing the magnitude of change in microbial taxonomy and function to HABs difficult.…”
Section: Introductionmentioning
confidence: 69%
“…These bacteria, archaea, and heterotrophic eukaryotes are particularly important for remineralizing bloom-derived organic matter (Buchan et al, 2014). Previous work has identified consistent taxonomic shifts in portions of the heterotrophic community in response to 'typical' sized blooms (Teeling et al, 2016;Wilson et al, 2021) and succession in the bacterial community has been observed following a HAB of Heterosigma akashiwo (Matcher et al, 2021). In particular, members of Flavobacteriales (Kirchman, 2002;Avci et al, 2020;Ferrer-Gonzalez et al, 2020;Matcher et al, 2021;Wilson et al, 2021) and Rhodobacterales Buchan et al, 2014) have both been shown to increase in response to phytoplankton-derived polysaccharides from variously sized blooms.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, it should be highlighted that H. akashiwo does not have a shell like most of the algae species, but it has amorphous vesicles under the cell wall. H. akashiwo has a mixed form of feeding, which includes photosynthesis, direct nutrition uptake, and the eating of bacterium [62].…”
Section: Microalga Culturementioning
confidence: 99%
“…Some species like Heterosigma akashiwo (Raphidophyceae) and Chaetoceros spp. (Diatomea) eventually form blooms in coastal areas through local and seasonal massive growth (Buchan et al, 2014;Needham and Fuhrman, 2016;Tomaru et al, 2018;Matcher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%